Fabrication and characterization of PVDF-based coatings for self-cleaning applications - Wong, Yi Chao (2015)
The discovery of lotus effect has led to the intensive research and development of materials that have superhydrophobic property for self-cleaning applications. Low surface energy and surface roughness are the two main parameters that contribute to hydrophobicity. Although there have been several studies on producing superhydrophobic coatings using polyvinylidene fluoride (PVDF), there were problems with adhesion between the coating and substrates. This experiment aimed to find out the solution to improve the adhesion between PVDF-based coating and the substrate while ensuring that the coating was superhydrophobic. Superhydrophobic coating was prepared with silica nanoparticles as the particulate fillers dispersed in the PVDF matrix. The coating solution was drop-cast onto substrates and cured at 100°C. Hydrophobicity was determined by measuring contact angle and sliding angle. The coating was characterized by roughness measurement, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscope (SEM), nanoindentation measurements, cross hatch adhesion test and self-cleaning test. Superhydrophobic coating with water contact angle of 151.33° and sliding angle <1° was created using 1:1 volume ratio of APTES solution to 5 wt% silica and 10 wt% PVDF in DMF and FAS solution. The morphology of the coating showed evenly distributed silica nanoparticles and nano-pores, which caused the superhydrophobicity. The coatings also showed improved adhesion and hardness due to the addition of APTES solution. Thus, this experiment has provided a feasible method for producing superhydrophobic PVDF-based coatings with good mechanical properties for self-cleaning applications. Further experiments can be done to find out other methods to produce rough coating surfaces and also improve transparency in order to widen the applications.